Nutritional status and dietary habits in older adults with fixed implant dental prostheses: a case-control study - Homsi, George; Trulsson, Mats; Grigoriadis, Anastasios; Kumar, Abhishek (Frontiers in Nutrition, 2024)
Aim: To evaluate the nutritional status, nutritional risk, and dietary habits of patients treated with bimaxillary implant-supported fixed prostheses in comparison with a group of natural dentate patients. Methods: A study group (n=25, 8 women, mean age = 70.6 ± 7.5 years) with bimaxillary implant-supported fixed prostheses and a control group (n=25, 13 women, mean age = 69.0 ± 5.3) with a mean of 27.7 ± 1.8 natural teeth were recruited. The nutritional status and nutritional risk of the participants were evaluated with Mini Nutritional Assessment (MNA) and Seniors in the Community: Risk Evaluation for Eating and Nutrition; (SCREEN-14), while the dietary habits were recorded by data from a three-day dietary record. The data were analyzed with the Mann-Whitney U-test and independent t-test to evaluate the differences between the groups. Results: The results showed that although both the groups had normal nutrition status as revealed by the MNA scores the study group showed significantly higher BMI (P=0.005) but lower SCREEN-14 (P=0.012) scores, than the control group. The results also showed that higher SCREEN-14 scores were significantly associated with higher odds of being in the control group, with an odds ratio of 1.159 (P = 0.024). Further, the results of the analysis of the dietary records showed that the participants in the study group consumed fewer meals (P=0.006) and fewer varieties of food (P<0.001), particularly fewer fruits (P=0.011) than the control group. Conclusion: The results indicate that people with fixed implant prostheses may be susceptible to nutritional deficiencies according to the SCREEN-14 scores compared to their natural dentate counterparts. Further, people with implant prostheses also tend to have higher BMI and consume a smaller variety of foods, especially fruits, than the natural dentate control group.